2008
DOI: 10.1093/treephys/28.2.265
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the decline in daily maximum transpiration rate of two pine stands during drought based on constant minimum leaf water potential and plant hydraulic conductance

Abstract: The effect of drought on forest water use is often estimated with models, but comprehensive models require many parameters, and simple models may not be sufficiently flexible. Many tree species, Pinus species in particular, have been shown to maintain a constant minimum leaf water potential above the critical threshold for xylem embolism during drought. In such cases, prediction of the relative decline in daily maximum transpiration rate with decreasing soil water content is relatively straightforward. We cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
75
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 82 publications
11
75
0
Order By: Relevance
“…This is consistent with other studies in pines that have shown that (1) a strong relationship between transpiration and soil moisture is also found at a depth of 0-25 cm [53] and (2) even if water can be extracted from deep layers, the topsoil layers, where most roots are located, have a larger influence on the rate of water uptake [54]. Compared to P. sylvestris, Q. ilex showed lower ΨPD and a steeper decline of this variable with decreasing SWC.…”
Section: Contrasting Hydraulic Strategies In P Sylvestris and Q Ilexsupporting
confidence: 93%
“…This is consistent with other studies in pines that have shown that (1) a strong relationship between transpiration and soil moisture is also found at a depth of 0-25 cm [53] and (2) even if water can be extracted from deep layers, the topsoil layers, where most roots are located, have a larger influence on the rate of water uptake [54]. Compared to P. sylvestris, Q. ilex showed lower ΨPD and a steeper decline of this variable with decreasing SWC.…”
Section: Contrasting Hydraulic Strategies In P Sylvestris and Q Ilexsupporting
confidence: 93%
“…The extreme autumns in terms of soil moisture content were 1998 (moist) and 2002 (dry and cold). In summer 2006 the forest was suffering from intensive drought (not shown), which reduced both the ecosystem respiration and gross photosynthesis and turned the stand to be a carbon source (Duursma et al, 2007) over two weeks in August. As a consequence, the early autumn (September-October) 2006 has the lowest θ values but in November the soil moisture content returned to the typical level.…”
Section: Seasonality and Environmental Controllersmentioning
confidence: 99%
“…The soil-to-root resistance (MPa s m 2 (ground) mol −1 ) is estimated with the single root model of Gardner (1960) (see Williams et al, 2001a andDuursma et al, 2008 for more details). This model estimates the effective path length for water transport through the soil matrix to the root surface from the fine root density.…”
Section: Hydraulics Of the Soil-to-leaf Pathwaymentioning
confidence: 99%
“…Although k P typically does decrease during drought due to formation of air-filled vessels (Sperry ,2000), Duursma et al (2008) showed that a model assuming a fixed k P was successful in predicting the response of plant water use to water limitation, in part because the soil resistance becomes limiting to water transport (Fisher et al, 2006). Nonetheless, gradual reduction in k P during drought is often an important determinant of plant water use (Sperry et al, 1998;Hacke et al, 2000).…”
Section: Uncertainty In Process Representationmentioning
confidence: 99%